Growth and fruiting of trees in intensive dwarf apple orchards depending on variety-rootstock combinations and planting density. - Yunusov Rustam; Ganieva Feruza Amrullovna; Artikova Manzura Israilovna (Zien Journals, 2022)
This article presents the results of a study inconditions of the horticultural economy of Siyovush Agro LLC, located on the territory of the Bogi Kalon MGS of the Bukhara region, Bukhara district, where the influence of variety-rootstock combinations and tree planting density on the growth, development and formation of yield elements was studied. Fruit trees in an intensive apple orchard have been scientifically studied during 2020-2022. A scientific experiment was carried out in young apple orchards, the Goldspur variety was planted on a weakly growing rootstock M-9, with a planting pattern of 4.0x1.0m, 4.0x1.2m, 4.0x1.4m, 4.0x1.6m, 4.0x1, 8m, and 4.0x2.0m, which are arranged in order, and as a result of the growth of the apple tree, the development and optimal formation of the elements of fruit formation, the phytometric indicators of illumination, the optimal arrangement of branches,
Keywords: Intensive orchard; fruit trees; dwarf apple trees; varietal rootstock combinations